Protective Mechanism of Sea buckthorn Proanthocyanidins Against Hydrogen Peroxide-Introduced Oxidative Damage in Adult Retinal Pigment Epithelial-19 - Kaiyuan Ma; Michael Yuen; Tina Yuen; Hywel Yuen; Qiang Peng (MDPI AG, 2024)
Retinal pigment epithelial (RPE) is an oxidation-resistant cell. But if it is subjected to various harmful stimuli for a prolonged period, an excessive amount of oxyradical will be generated to cause retinal dysfunction. We investigated and elucidated the protective mechanism of Sea buckthorn proanthocyanidins (SBP) against oxidative damage in RPE. In this study, we established an oxidative damage model of adult retinal pigment epithelial cell line-19 (ARPE-19) using hydrogen peroxide (H2O2), followed by different concentrations of SBP for 24 h. The finding demonstrated that SBP effectively inhibited the generation of malondialdehyde (MDA), restored the activity of superoxide dismutase (SOD) and content of glutathione (GSH), and significantly eliminated the level of reactive oxygen species (ROS) and oxidative stress. It was revealed that 100 µg/mL of SBP was more suitable for restoring oxidative damage in ARPE-19, which enhanced cell activity and migration ability and maintained normal cell morphology. In addition, SBP increased the expression of Bcl-2, decreased the expression of Bax and caspase-3, and activated the Nrf2/HO-1 signaling pathway to protect ARPE-19 from oxidative stress. Moreover, SBP could restore the morphology and quantity of mitochondria and inhibit mitochondrial permeability and swelling. The present results provide a theoretical basis for the protective and restorative effect of SBP in retinopathy caused by oxidative stress.